STRATEGI PEMBERDAYAAN MASYARAKAT DALAM PENANGGULANGAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN ROKAN HILIR - Dani, Rahmad; Yoza, Defri; Sulaeman, Rudianda (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to determine the socio-economic conditions of people who become the root causes of forest fires and field, obtain information efforts to control forest fires and land that has been done by the public and develop appropriate strategies to empower communities in the implementation of the prevention of forest fires in Rokan Hilir. This research is descriptive. The collection of data on community empowerment strategies in the prevention of forest fires and field with interviews and direct observations. The analysis used in this study is a descriptive analysis using analytical techniques and percentage SWOT analysis. The social conditions that influence the occurrence of forest and field fires in Rokan Hilir is the level of the majority of people who are not in school and worked as a farmer clearing by culture and economic situation of people who lands <2 hectare burning education. Forest fire prevention efforts undertaken by the field is public worked together to set fire using simple tools and semi-mechanical tools. Community empowerment strategies for the prevention of forest fires and land is established good cooperation among agencies, improve people skills, develop types of horticultural crops pineapple, using their areas, the government socialize penalty facilitate the heavy equipment and additional suppression of forest fires and strict enforcement tools.   Keywords: Community development, prevention of forest fires and field